Evaluation of farmers' participatory behavior and compensation policy for agricultural water-saving - Mirzaei, Abbas; Azarm, Hassan (Frontiers in Water, 2022)
Today, with the decreased available water resources and the intensification of the conflicts between users of water resources, the cooperation or non-cooperation of users in water protection programs, especially in the agricultural sector, is of crucial importance. Therefore, the present study is aimed to provide a framework to evaluate the participatory behavior of farmers with optimal patterns of water allocation and to estimate the necessary budget to compensate for the reduction of water consumption in agricultural areas. To achieve this aim, the integration of the economic-environmental programming model with a top-down analytical approach and the agent-based model with a bottom-up analytical approach has been applied in the present study. Thus, the irrigation network of Jiroft Plain was chosen as the study area and a sample of farmers in this irrigation network was extracted for the analysis of the agent-based model using simple random method. It was found that different forms of insistence on the individual behavior of farmers make it difficult to participate in optimal water allocation patterns with simultaneously providing economic and environmental goals. As the degree of participation with the optimal model of water allocation with equal weight to economic and environmental goals, despite the implementation of the policy of giving facilities with a very low interest rate for the installation of new irrigation technologies, is estimated about 20%. Finally, the necessary budget for compensation policy for agricultural water storage was calculated based on the proposed framework, which can be considered a useful tool for policy makers in water resources management.